Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/jcm9030755
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Subjective Symptoms and Tolerability in Response to Nintedanib Treatment in Elderly Patients with Idiopathic Pulmonary Fibrosis

Abstract: The efficacy of nintedanib treatment in patients with idiopathic pulmonary fibrosis (IPF) was demonstrated in phase III trials. However, there is limited data on the significance of nintedanib in elderly patients aged ≥75 years. We have retrospectively evaluated 54 newly nintedanib-treated patients including 32 elderly individuals. Potential changes in modified medical research council (mMRC) grade and COPD (chronic obstructive pulmonary disease) assessment test (CAT) score, as well as in forced vital capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…It is surely interesting that, despite the age discrepancy, no significant differences were found between pirfenidone and nintedanib subgroups in terms of progression-free survival and mortality. These findings further support the substantial efficacy of antifibrotic drugs and specifically of nintedanib, also in elderly age, as already reported in literature ( Takeda et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…It is surely interesting that, despite the age discrepancy, no significant differences were found between pirfenidone and nintedanib subgroups in terms of progression-free survival and mortality. These findings further support the substantial efficacy of antifibrotic drugs and specifically of nintedanib, also in elderly age, as already reported in literature ( Takeda et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Additional post-hoc analysis of INPULSIS trials indicated that the efficacy of nintedanib was not affected by age (< 65, or ≥ 65 years old) [ 23 ]. Takeda et al reported that nintedanib also improves subjective improvement, as well as FVC decline in elderly IPF patients [ 18 ]. These studies suggest that nintedanib is effective for elderly IPF patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of onset is 70 (standard deviation [SD]: 9.0) years in Japan [ 6 ]. However, the available data on the tolerability and efficacy of nintedanib in elderly patients in the real-world are limited [ 18 ]. The mean age of patients who were treated with nintedanib in a real-world setting was 66.6 (SD: 8.1) years in the INPULSIS trials [ 11 ], 71 (SD: 8) years in the USA [ 19 ], and 71.8 (SD: 7.5) years in Greece [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nintedanib and pirfenidone are oral anti-fibrotic drugs used to slow the progression of idiopathic pulmonary fibrosis (IPF). A number of recent “real-world”, observational, and retrospective studies ( Antoniou et al, 2020 [C]; Cameli et al, 2020 [C]; Chung et al, 2020 [C]; Corral et al, 2020 [C]; Dhooria et al, 2020 [C]; Eaden et al, 2020 [C]; Harari et al, 2020 [c]; Justet et al, 2021 [c]; Lasky et al, 2020 [C]; Majewski et al, 2020 [C]; Senoo et al, 2020 [c]; Takeda et al, 2020 [c]; Uchida et al, 2021 [c]; Vianello et al, 2020 [c]), an open-label extension study ( Song et al, 2020 [C]), a small, prospective, patient-satisfaction study ( Moor et al, 2020 [c], and a post-hoc analysis ( Richeldi et al, 2020 [C]) further describe the safety profile of these drugs among patients with IPF from different nations, with more advanced disease, with advanced age, or who have been switched from nintedanib to pirfenidone. In these studies, the type, frequency, and severity of adverse drug events were similar to previously published clinical trial results and showed no new signals of adverse drug events with either nintedanib or pirfenidone.…”
Section: Anti-fibrotic Therapies [Seda-40 224; Seda-41 177; Seda-42 175]mentioning
confidence: 99%